2001
DOI: 10.1093/ajcn/74.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic evidence of no harmful effect of oats in celiac disease

Abstract: Because the in vitro challenge with PT-avenin and its C fraction did not induce EMA production in treated celiac disease patients, it appears that oats have no harmful effect on celiac disease. Therefore, oats can be safely included in a gluten-free diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 21 publications
2
36
0
3
Order By: Relevance
“…Some patients may consume large quantities of oats in order to improve a restricted diet. The statement from earlier studies (Janatuinen et al, 1995(Janatuinen et al, , 2000(Janatuinen et al, , 2002Srinivasan et al, 1996;Hardman et al, 1997;Reunala et al, 1999;Picarelli et al, 2001) that a 'moderate quantity of oats is safe', may lead to misinterpretation and confusion. Results from this study on 20 adult coeliac patients in remission indicate that there is no reason to state that intake of uncontaminated oats in adults must be limited to small or moderate amounts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients may consume large quantities of oats in order to improve a restricted diet. The statement from earlier studies (Janatuinen et al, 1995(Janatuinen et al, , 2000(Janatuinen et al, , 2002Srinivasan et al, 1996;Hardman et al, 1997;Reunala et al, 1999;Picarelli et al, 2001) that a 'moderate quantity of oats is safe', may lead to misinterpretation and confusion. Results from this study on 20 adult coeliac patients in remission indicate that there is no reason to state that intake of uncontaminated oats in adults must be limited to small or moderate amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the 1950s reported raised levels of faecal fat or reduced xylose excretion in a few patients who consumed large amounts of oats ( > 60 -70 g=day; Dicke et al, 1953;Moulton, 1959;Baker & Read, 1976). Recent research, however, suggests that moderate amounts of oats, ie about 50 g=day, can be safely consumed by adult coeliac patients as well as subjects with dermatitis herpetiformis (Janatuinen et al, 1995(Janatuinen et al, , 2000Srinivasan et al, 1996;Hardman et al, 1997;Reunala et al, 1998;Picarelli et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…were not present in avenin (Picarelli 2001). Kilamartin et al, showed that in vitro challenge with avenin did not induce production of EMA (Kilamartin 2003).…”
Section: Treatment Gfd: Now and Then-oatsmentioning
confidence: 99%
“…Rye and barley show some degree of 'toxicity' in CD, whereas rice and maize have generally been considered safe for celiac patients (Dicke et al 1953;Cornell and Townley 1974;Baker and Read 1976;Anand et al 1978). Furthermore, recent works have provided impressive results showing that oats is tolerated by CD patients, with the only exception of certain individuals possessing peculiar DQ2-restricted T cells (Picarelli et al 2001;Janatuinen et al 2002;Kilmartin et al 2003;Arentz-Hansen et al 2004). More interestingly, large differences in the harmfulness profile of prolamins have been found in the genus Triticum, which contains diploid, tetraploid and hexaploid species.…”
Section: Introductionmentioning
confidence: 99%